PERAN IBU RUMAH TANGGA DALAM PEMBERDAYAAN SOSIAL: PERSPEKTIF FEMINISME MARXIS - Samosir, Sry Lestari (DAS Institute, 2024)
This study aims to analyze the strategic role of housewives in social empowerment through the lens of Marxist feminism. In a social system dominated by patriarchal norms, housewives are often positioned as domestic actors without formal recognition of their contributions to the capitalist economic structure. However, they play multifaceted roles in supporting family economic sustainability and social reproduction. This study employs a qualitative approach with a case study design, involving in-depth interviews, and observations, of housewives in Medan City who are engaged in community activities and home-based micro-enterprises. The findings reveal that housewives contribute to social reproduction through domestic labor and active community participation. Activities such as skill training and self-employment not only enhance family welfare but also foster social solidarity. However, their roles are often constrained by structural barriers, such as gender stereotypes and patriarchal dominance in decision-making. This study concludes that housewives hold significant potential as agents of social change, which can be maximized through interventions supporting their participation in public spheres